2007
DOI: 10.1227/01.neu.0000289714.18297.41
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Image Guidance for Open Vascular Neurosurgery Using Digital Angiographic Roadmapping

Abstract: Angiographic roadmapping is an effective intraoperative navigation tool for resection of vascular lesions that has not been previously described and offers several advantages to frameless stereotaxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…4 A portable vascular C-arm has also been used to create an angiographic road map by using DSA to guide open cerebrovascular procedures as a form of neuronavigation. 3 Rotational 3D DSA provides more information about complex cerebrovascular anatomical detail than conventional DSA. 1,5,17,19,22 The 3D DSA images are reconstructed from 2 separate rotational angiography acquisitions: a mask run and a contrast run.…”
Section: Discussionmentioning
confidence: 99%
“…4 A portable vascular C-arm has also been used to create an angiographic road map by using DSA to guide open cerebrovascular procedures as a form of neuronavigation. 3 Rotational 3D DSA provides more information about complex cerebrovascular anatomical detail than conventional DSA. 1,5,17,19,22 The 3D DSA images are reconstructed from 2 separate rotational angiography acquisitions: a mask run and a contrast run.…”
Section: Discussionmentioning
confidence: 99%
“…Finally superficial landmarks on the surface of the brain or at the resection site can help in the exact localization of a possible residual AVM. 2 Murayama et al 11 described their initial experience with an endovascular operating suite and confirmed its effectiveness and practicality in intracranial vascular procedures. However, they did not report the use of intraoperative rotational 3D angiography.…”
Section: Discussionmentioning
confidence: 92%
“…Intraoperative angiography has been widely used during brain operations mainly for the therapy of complex AVMs and has been shown in several cases that the procedure was altered because of the knowledge provided by intraoperative angiography [5 -7] . Furthermore, several studies have proven that intraoperative angiography provides a useful tool also in spinal AVM surgery for roadmapping the lesion [1] or for the detection of residual feeding arteries [3,4] . In several cases, intraoperative angiography led to a change of the surgical procedure as well [8] .…”
Section: Discussion ▼mentioning
confidence: 99%